Specialist palliative for patients with cancer: more than end-of-life care - Davies, Andrew (My University, 2023)
Palliative care has traditionally focused on end-of-life care for patients with advanced cancer. This has since expanded to include symptom management and quality-of-life improvement from the moment of cancer diagnosis. Specialist palliative care teams work across community and inpatient settings and focus on dealing with complex problems whilst supporting healthcare colleagues in providing generalist palliative care. This article will outline the principles of palliative care, models of palliative care delivery, the distinctions between palliative care and supportive care, and the role of specialist palliative care in cancer survivorship.
PUBLISHED
Keywords: cancer; holistic care; palliative care; supportive care; Cancer; Palliative Medicine